Effect of microencapsulated butyric acid supplementation on growth performance, ileal digestibility of protein, duodenal morphology and immunity in broilers - IMRAN, M.; AHMED, S.; DITTA, Y. A.; MEHMOOD, S.; KHAN, M. I.; GILLANI, S. S.; RASOOL, Z.; SOHAIL, M. L.; MUSHTAQ, A.; UMAR, S. (Journal of the Hellenic Veterinary Medical Society, 2018)
This experiment was conducted to evaluate the effect of microencapsulated butyric (MEB) acid on growth performance, apparent ileal digestibility of protein (AID), duodenal morphology and immunity in broilers reared to 35-days. In total, 336 one-day-old Hubbard classic broiler chicks were randomly assigned to 4 dietary treatments (Control, 0.25, 0.35 and 0.45g/kg of MEB). Each treatment was replicated 3 times with 28 birds in each replicate. Feed intake, body weight gain and feed conversion ratio (FCR), parameters of growth performance and intestinal morphology, AID of protein and immunity parameters were evaluated. At the end of the experiment (35-d), 3 birds / replicate were randomly selected and slaughtered to collect blood, duodenal samples, and ileal digesta. The result indicated improved body weight gain (P<0.05), feed conversion ratio (P<0.05) and AID (P<0.05) whereas, treatments remained unresponsive with respect to feed intake (P>0.05), duodenal villous height (P>0.05) and antibody titer against Newcastle disease (ND) (P>0.05). There is an indication that MEB improves the digestion and consequently bird’s performance.